2023
DOI: 10.1371/journal.pgen.1010450
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal extension of Arabidopsis ARGONAUTE 1 is essential for microRNA activities

Abstract: microRNAs (miRNAs) regulate target gene expression through their ARGONAUTE (AGO) effector protein, mainly AGO1 in Arabidopsis thaliana. In addition to the highly conserved N, PAZ, MID and PIWI domains with known roles in RNA silencing, AGO1 contains a long, unstructured N-terminal extension (NTE) of little-known function. Here, we show that the NTE is indispensable for the functions of Arabidopsis AGO1, as a lack of the NTE leads to seedling lethality. Within the NTE, the region containing amino acids (a.a.) 9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…We have also shown that the presence of sDMA modifications is not essential for AtAGO1 miRNA loading and for AtAGO1-dependent SUL silencing triggered by the pSUC2-amiRSUL construct. Our results are consistent with Xu et al who concluded ( 24 ) that the first 90 aa of AtAGO1, which includes 8 out of the 9 RGG/GRG motifs, are not required for miRNA association. In fact, we rather underscore a specific role in the regulation of a subset of 21nt-long siRNAs in prmt5 , mainly originated from genes, and previously identified as phasiRNA ( 57 , 58 , 69 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We have also shown that the presence of sDMA modifications is not essential for AtAGO1 miRNA loading and for AtAGO1-dependent SUL silencing triggered by the pSUC2-amiRSUL construct. Our results are consistent with Xu et al who concluded ( 24 ) that the first 90 aa of AtAGO1, which includes 8 out of the 9 RGG/GRG motifs, are not required for miRNA association. In fact, we rather underscore a specific role in the regulation of a subset of 21nt-long siRNAs in prmt5 , mainly originated from genes, and previously identified as phasiRNA ( 57 , 58 , 69 ).…”
Section: Discussionsupporting
confidence: 93%
“…The N-terminal extensions (NTE) of AGO proteins have been recently analysed in several works ( 17 , 21 , 22 , 24 ) highlighting the main interest on understanding the role of this poorly described region in AGO activity. Our study launches the question of the regulation of AGO1 protein in A. thaliana with a particular emphasis on the role of its NTE, which contains predicted Glycine-Arginine Rich (RGG/GRG) recognition sites for PRMT5 enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Poly-Q domain contains several RGG/RG motifs (Xu et al, 2023) recognized as RNA binding motifs (Thandapani et al, 2013), we then investigated whether the presence of RNA had an influence on LLPS. Interestingly, recombinant GFP- Poly-Q domain AGO1 protein could efficiently bind 112nt long single-stranded and double-stranded RNA in electrophoretic mobility assays (EMSA) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, a recent study in A. thaliana demonstrates that plant AGO1 contains an unstructured N-terminal region (named NTE for N-terminal extension in this study) important for plant viability as well as miRNA stability and loading. (78). This new observation in plants strengthens our ideas that the N-terminal region of AGO is crucial for miRNA loading, and the mechanism we uncovered is likely widespread across different species.…”
Section: Discussionmentioning
confidence: 99%